Study on blaKPC gene among Klebsiella pneumoniae from the Clinical Specimens in a Tertiary Care Hospital, Kathmandu, Nepal - Khadka, Shusila; Adhikari, Ram Prasad; Khanal, Laxmi Kant; Pandey, Ritu; Sah, Anil Kumar; Sapkota, Jyotshna (Nepal Medical College Journal, 2025)
Multidrug resistance (MDR) among Klebsiella pneumoniae: a common nosocomial pathogen, has been a great concern for managing its infections effectively worldwide. Production of KPCs (Klebsiella pneumoniae carbapenemases) is one of the most important mechanisms in this bacterium, making it resistant to carbapenems: the most commonly used antibiotics for treating MDR organisms. This study was done to detect KPC genotypes (blaKPC-1, blaKPC-2, blaKPC-3) among K. pneumoniae isolates and to determine their antimicrobial susceptibility patterns.A descriptive cross-sectional study was conducted from September 2023 to February 2024 in a total of 82 non-repetitive clinical isolates of K. pneumoniae at Clinical Microbiology Laboratory of Nepal Medical College Teaching Hospital (NMCTH), Nepal. More than one-third (30/82; 36.58%) of the isolates were MDR. Out of the total isolates, 18 (21.95%) were resistant to carbapenems. Of these, 14 (77.77%) isolates possessed blaKPC-2 gene. All isolates were susceptible to Polymyxin and Colistin sulphate. Almost half of the isolates were resistant to Cephalophorins (Cefixime- 43.90%, Ceftriaxone-41.0% and Ceftazidime-43.9%). Presence of KPC producing K. pneumoniae isolates in our set-up, with higher level of resistance to multiple antibiotics highlights the need for continuous monitoring and endorsement of control strategies to tackle the challenges created by this bacterial pathogen.